Ultrasound-Guided Serratus Anterior Plane Block for Pain Management Following Minimally Invasive Repair of Pectus Excavatum - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2019)
Objective: The Nuss procedure is a preferred technique for minimally invasive repair of pectus excavatum (MIRPE), but it is associated with significant postoperative pain. We assessed the efficacy and safety of an ultrasound-guided bilateral serratus anterior plane block (SAPB) for relieving acute pain from MIRPE. Design: A retrospective cohort study. Setting: This study was conducted at the Marmara University Pendik Training and Research Hospital, Turkey. Participants: All participants were scheduled for MIRPE. Interventions: This study was conducted from November 2017 to May 2018. Postoperative pain control was achieved with bilateral SAPB done after induction of anesthesia and IV PCA in 50 patient (SABP group) and with only IV PCA in 45 patients (Control group). SAPB was achieved, targeting the interfascial plane between the serratus anterior and latissimus dorsi muscles, with a single injection of 30 mL (20 mL if patient weighed < 40 kg) of 0.25% bupivacaine and 0.5% lidocaine into each side. Pain scores were recorded for 24 h. Measurement and Main Results: Patients in the Control group had a higher demand (mean difference, 61; 95% confidence interval [CI] 30.5-136; P < 0.0001) and delivery dose (mean difference, 25; 95% Cl 15-41.5 P = 0.001) during the first postoperative 24 h. SAPB did not affect the median (interquartile range) length of hospital stay: 5 (5-7) days vs. 5 (4-6) days, (P = 0.085). Conclusions: Bilateral single-injection SAPB in patients undergoing MIRPE decreases pain and opioid consumption during the early postoperative period. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: Pectus excavatum; Pain management; Serratus anterior plane block; Nuss procedure; analgesia; PATIENT-CONTROLLED ANALGESIA; THORACIC EPIDURAL ANALGESIA; POSTOPERATIVE PAIN; NUSS PROCEDURE; PEDIATRIC-PATIENTS; OUTCOMES; THORACOTOMY; CATHETERS